Macromineral and trace element concentrations and their seasonal variation in milk from organic and conventional dairy herds. (15th October 2021) - Qin, Nanbing; Faludi, Gergely; Beauclercq, Stephane; Pitt, Joe; Desnica, Natasa; Pétursdóttir, Ásta; Newton, Eric E.; Angelidis, Angelos; Givens, Ian; Juniper, Darren; Humphries, David; Gunnlaugsdóttir, Helga; et al.
Highlights: Mineral profiles of conventional and organic milk were measured. Organic milk contained more Ca, K, P and Mo than conventional milk. Organic milk contained less Cu, Mn and Zn than conventional milk. Organic milk had a lower I concentration than conventional milk in June and July. Cow diets and breeds are main drivers for the concentrations of most milk minerals. Abstract: To study the effects of dairy production system on milk macromineral and trace element concentrations, milk samples were collected monthly in 2019 from 43 conventional and 27 organic farms. Organic milk contained more Ca (1049.5 vs. 995.8 mg/kg), K (1383.6 vs. 1362.4 mg/kg), P (806.5 vs. 792.5 mg/kg) and Mo (73.3 vs. 60.6 μg/kg) but less Cu (52.4 vs. 60.6 μg/kg), Fe (0.66 vs 2.03 mg/kg), Mn (28.8 vs. 45.0 μg/kg), Zn (4.51 vs. 5.00 mg/kg) and Al (0.32 vs. 1.14 μg/kg) than conventional milk. Significant seasonal variation was observed in all determined minerals' concentrations. Milk I concentration was not consistently affected by production system, whereas organic milk contained less I in June and July than conventional milk. Dietary factors contributing to different milk mineral concentrations between production systems included intakes of maize silage, dry-straights and oils (higher in conventional diets), and pasture, clover and wholecrop (higher in organic diets).